2021
DOI: 10.1016/j.cmi.2020.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric evaluation of BioFire FilmArray Pneumonia Panel for rapid bacteriological documentation of pneumonia

Abstract: Objectives: To evaluate performances of the rapid multiplex PCR assay BioFire FilmArray Pneumonia Panel (FA-PP) for detection of bacterial pathogens and antibiotic resistance genes in sputum, endotracheal aspirate (ETA) and bronchoalveolar lavage (BAL) specimens. Methods: This prospective observational study was conducted in 11 French university hospitals (July to December 2018) and assessed performance of FA-PP by comparison with routine conventional methods. Results: A total of 515 respiratory specimens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 23 publications
6
43
1
3
Order By: Relevance
“…In our study, the mPCR provided good overall performance for bacteria, with a PPV of 85.6% which is above what has been found in previous studies (between 46.9 and 79.6%) and an NPV of 99.5% which is consistent with previous studies [10][11][12][13]. Other studies showed positive and negative percentage agreement of mPCR compared to culture between 90 and 98.4% and 96 and 97% respectively [9,12,14].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, the mPCR provided good overall performance for bacteria, with a PPV of 85.6% which is above what has been found in previous studies (between 46.9 and 79.6%) and an NPV of 99.5% which is consistent with previous studies [10][11][12][13]. Other studies showed positive and negative percentage agreement of mPCR compared to culture between 90 and 98.4% and 96 and 97% respectively [9,12,14].…”
Section: Discussionsupporting
confidence: 91%
“…However, bacterial panel is not exhaustive and can miss some species causing HAP or VAP such as M. morganii or S. maltophilia. We also observed that in some cases, bacteria were detected by culture and not by mPCR, which was already described previously, since the manufacturer threshold is 10 3.5 genomic copies/mL [12,15]. On the other hand, we observed that, when the bacteria were only detected by mPCR, the patients had received antibiotics active on these germs in the previous days, which could explain why they were not found in culture.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Lee et al demonstrated a PPA of 90% and NPA of 97.4% as compared to SOC bacteria detection, with BioFire PN Panel identifying a pathogen in 47.4% of BLS and in 60% of SLS for an overall positivity rate of 55.93% [24]. Edin demonstrated for on-panel pathogens a PPA of 100% and an NPA of 73.2% [25], and Gastli demonstrated a PPA of 94.4% and an NPA of 96.0% as compared to culture [26]. Similarly, a VAP study using a research use only version of BioFire PNplus Panel demonstrated for bacteria an 89.0% PPA and 95.9% NPA with SOC [27].…”
Section: Number and Type Of Microorganisms Reported By Soc Notmentioning
confidence: 99%
“…Molecular tests based on multiplex PCR have been developed to simultaneously detect and quantify multiple respiratory pathogens, as well as some genes related to antimicrobial resistance. Several commercial multiplex platforms are currently available for comprehensive molecular testing for respiratory pathogens that cause pneumonia (respiratory viruses, bacteria and fungi) and for the main resistance genes of the most common bacteria causing pneumonia [195][196][197][198] .…”
Section: Microbiology and Laboratory Testsmentioning
confidence: 99%